Effects of Hypericum perforatum on serum lipid vascular systems in mice - Zena S. Hamed; Rana R. Abed; Mohammed S. Almashhadany; Marwan M. Merkhan (Iraqi Journal of Veterinary Sciences, 2022)
Herbal products are increasingly used against lipid to attenuate its negative impact on vasculature system. However, there are uncertainty regarding the best administration approaches and preparation of herbal product to be used due to variation in absorption rate and extent with subsequent impaction on the lipid levels. The aim of the present study was comparing the pharmacological and analytical aspects of soaked versus powder form of Hypericum perforatum; a well-known anti-hyperlipidemic herbal product, using atorvastatin drug as a reference drug for comparison in addition to controlling groups (on/off lipid diet) handled as an additional control group. To conduct this research, the hyperlipidemia mice models were created by exposing the mice to a fatty diet and using H. perforatum and atorvastatin for evaluation. The plant extracts were also analyzed for active constituents. The results indicate that the plant analysis detected the presence of different antihyperlipidemic agents and the plant has effectively reduced plasma lipid parameters in exposed mice compared to control group; especially when taken forms of the plant was used. The study concluded that; soaked H. perforatum extract shown an effective reduction of lipid parameters and analysis of which revealed the presence of herbal active constituent which might be utilized in industrial pharmacy for new drug innovation.